ALKENONE-SEA SURFACE TEMPERATURES IN THE JAPAN SEA OVER THE PAST 36 KYR: WARM TEMPERATURES AT THE LAST GLACIAL MAXIMUM - Ishiwatari R.; Houtatsu M.; Okada H. (My University, 2001)
The Japan Sea experienced bottom water anoxia at the last glacial maximum (LGM) since it is surrounded by four shallow straits, the sill depths of which are close to, or shallower than, the drop in sea level (∼120 m) that occurred then. A distinctive negative δ18O excursion of planktonic foraminifera also took place during the LGM. This excursion has been interpreted from foraminiferal data as recording a drop in the paleosalinity of surface waters on the assumption of a constant low sea surface temperatures between 34 and 11 ka. We present here a profile of alkenone-based sea surface temperatures (alkenone-SSTs) over the past 36 kyr. Our results suggest that SSTs during the LGM were much higher than those previously assumed. After considering the factors that might affect estimation of alkenone-SSTs and comparisons of core-top alkenone-SSTs values with values for modern seawater we conclude that the higher alkenone-SSTs during the LGM are reliable and reasonable. These warm SSTs were probably caused by radiative equilibrium associated with the development of stable water stratification in the Japan Sea during the LGM.